Entropic analysis of human body’s longevity as a function of physical activity level - NOGUEIRA, INARA M.; COSTA JR, ESLY F.; COSTA, ANDRÉA O.S. (Anais da Academia Brasileira de Ciências, 2023)
The literature reveals the application of the laws of thermodynamics for predicting life span and the effects of the physical activity level on longevity. But the vastly simplified literature models seem to suggest a reduction in duration of life with increased activity level, which is the opposite of medical recommendations, that means that exercises increase the longevity. The main objectives of this paper are to re-present the previous model, check and confirm the previous results and improve the model by formulating a simplified phenomenological relation between life span, specific entropy generation of the body (SEG-life, in MJ/kg.K) and physical activity level. The model was validated considering different individuals. In this study, it is suggested that the principle of cumulative entropy generation limit should be relaxed in function of lifestyle and type of exercise performed during life, differently from what it is defined by the literature. So, it is proposed a relax to the limit on SEG-life as a result of various physical activity levels.The literature reveals the application of the laws of thermodynamics for predicting life span and the effects of the physical activity level on longevity. But the vastly simplified literature models seem to suggest a reduction in duration of life with increased activity level, which is the opposite of medical recommendations, that means that exercises increase the longevity. The main objectives of this paper are to re-present the previous model, check and confirm the previous results and improve the model by formulating a simplified phenomenological relation between life span, specific entropy generation of the body (SEG-life, in MJ/kg.K) and physical activity level. The model was validated considering different individuals. In this study, it is suggested that the principle of cumulative entropy generation limit should be relaxed in function of lifestyle and type of exercise performed during life, differently from what it is defined by the literature. So, it is proposed a relax to the limit on SEG-life as a result of various physical activity levels.